Large volume cryopreservation of lumpfish (Cyclopterus lumpus L.) sperm for commercial hatchery production - Opeifa, Bamidele Theophilus (UiT The Arctic University of Norway, 2019)
The growing Atlantic salmon (Salmo salar) aquaculture production is confronted with many challenges that limit the potential development of the industry. The major current problem threatening the salmon aquaculture production is the parasitic sea lice (Lepeophtheirus salmonis) that negatively affects both cultured salmon and wild stock populations. Several treatment options have failed to deliver universally accepted results without negative impacts on the fish or the environment. Therefore, the need for alternative solution made way for cleaner fish - lumpfish (Cycloptherus lumpus), a cold water species that can tolerate low temperatures without affecting its grazing capacity making it suitable for the biological control of sea lice infections in norther locations. Despite the interest, some bottlenecks need to be solved to allow a reliable and commercially sustainable year-round production of lumpfish juveniles, including broodstock management and related gametes’ availability issues. This study tries to establish a protocol for large volume cryo-preservation of lumpfish sperm for use under commercial production. The procedure involves cryopreservation of lumpfish sperm from crushed testes in a cryo-solution containing 10% DMSO diluted 50:50 in wolfish extender pre-frozen at two heights (2.5 cm and 4.8 cm) before storage in liquid nitrogen. Evaluation of sperm quality and viability was assessed based on single and combination of multiple criteria, including a) sperm motility parameters, b) functional integrity of sperms, and c) egg fertilization rates. Sperm concentration was measured through spermatocrit and the value varied widely between males, ranging 44-85%. The motility parameters (MOT, LIN, PROG and VCL) measured showed significantly reduced values between the control and treatment groups across all the parameters. The sperm quality measurement also followed a reduced pattern when comparison was made between percentages of motile sperm from CASA analysis with the percentage of live sperm cells evaluated ...